The THE SCRAMBLE METHOD TO IMPROVE MEMORIZING SKILLS ENGLISH TENSES TOP OF HEAD IN COMMUNITY SERVICE ACTIVITIES - Sa'diyah, Siti Halimatus; Laabidi, Hicham (LP3M Universitas Islam Zainul Hasan Genggong, 2024)
This community service activity aims to provide improvements to students using the scramble method as one of the main methods for improving the ability to memorize tenses in learning English grammar. The method used a descriptive qualitative approach with a type of case study. The research location is class XII Madrasah Aliyah Ihyaul Islam. While the data collection used in this study included direct observation and unstructured interviews to determine the accuracy of the data. The results obtained from using the scramble method, students experience an increase in memorizing and understanding the tenses formula because students are invited to actively think by answering the questions given in a group and then arranging the questions to form sentences according to the tenses formula. And the activity also with play activities between groups. So that students can have fun playing but still get the intended results.